2008
DOI: 10.1088/0031-8949/79/01/015501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-focusing on laser third harmonic generation in a clustered gas

Abstract: An intense Gaussian laser beam propagating through a gas embedded with atomic clusters creates a nanoplasma medium which supports self focusing of the laser beam. The laser beam produces a third harmonic due to nonlinear electron response. The efficiency of the process is sensitive to the focusing of the fundamental laser beam. The harmonic generation yield increases as the clusters expand under hydrodynamic pressure and attains a maximum at the instant when plasma density inside clusters equals three times th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Tiwari and Tripathi [33] have reported that much enhancement in third harmonic generation can be achieved when one has taken clustered radius 1.7 times than its initial radius. Parashar et al [34] proposed a theory of third harmonic generation in cluster plasma by Gaussian laser beam under paraxial ray approximation. It is found that self-focusing plays an important tool for efficient harmonic generation when cluster density is three times to its critical density.…”
Section: Introductionmentioning
confidence: 99%
“…Tiwari and Tripathi [33] have reported that much enhancement in third harmonic generation can be achieved when one has taken clustered radius 1.7 times than its initial radius. Parashar et al [34] proposed a theory of third harmonic generation in cluster plasma by Gaussian laser beam under paraxial ray approximation. It is found that self-focusing plays an important tool for efficient harmonic generation when cluster density is three times to its critical density.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts are being made by various researchers to investigate the interaction of a laser beam with clusters [24][25][26][27]. Tiwari and Tripathi [24] presented a study of third order harmonic generation from an exploding cluster.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that an increase in the ratio of nanoparticles' radii to their separation, and also enhancement in the maximum amplitude, lead to the localization of the laser beam transversely. Another analytical investigation of the self-focusing of a Gaussian laser beam propagating through a gas embedded with atomic clusters was presented by Parashar [26]. Vij [27] studied wiggler magnetic field assisted third harmonic generation of an intense short pulse laser in a cluster in its expanding phase.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It is observed that harmonic yield is significantly enhanced in the presence of surface roughness or nanostructures. [8][9][10][11][12][13][14] This enhancement is attributed to laser mode conversion into surface plasma wave (SPW), an electromagnetic mode, propagating close to metaldielectric interface with sharp decay of amplitude in both mediums away from the interface.…”
Section: Introductionmentioning
confidence: 99%